Storytelling in Northern Zambia Theory, Method, Practice and Other Necessary Fictions - Cancel, Robert (World Oral Literature Series, 2013)
More than just a book, Storytelling in Northern Zambia lets you watch videos of the storytellers while you read. Storytelling plays an important part in the vibrant cultural life of Zambia and in many other communities across Africa. This innovative book provides a collection and analysis of oral narrative traditions as practiced by five Bemba-speaking ethnic groups in Zambia. The integration of newly digitalised audio and video recordings into the text enables the reader to encounter the storytellers themselves and hear their narratives as they were recounted during Robert Cancel's research trips to Zambia. Robert Cancel's thorough critical interpretation, combined with these newly digitalised audio and video materials, makes Storytelling in Northern Zambia a much needed addition to the slender corpus of African folklore studies that deal with storytelling performance. Cancel threads his way between the complex demands of African fieldwork studies, folklore theory, narrative modes, reflexive description and simple documentation and succeeds in bringing to the reader a set of performers and their performances that are vivid, varied and instructive. He illustrates this living narrative tradition with a wide range of examples, and highlights the social status of narrators and the complex local identities that are at play. Cancel's innovative study tells us not only about storytelling but sheds light on the study of oral literatures throughout Africa and beyond. Its innovative format, meanwhile, explores new directions in the integration of primary source material into scholarly texts. This book is part of our World Oral Literature Series in conjunction with the World Oral Literature Project.